Fixed combination of tazarotene and betamethasone dipropionate for treatment of psoriasis vulgaris: The result of a phase 3, multicenter, randomized controlled trial. Issue 7 (28th April 2020) - Chen, Hao; Sun, Jianfang; Yang, Haizhen; Sun, Qiuning; Zhang, Jianzhong; Gu, Jun; Wen, Hai; Li, Ming; Liu, Xiaoming; Yang, Huilan; Lou, Donghua
Abstract: Long‐term use of corticosteroids or local use of tazarotene (TAZ) alone for the treatment of psoriasis cause safety issues and low compliance rates. Combining these two may optimize their efficacy and minimize safety concerns. This study aimed to evaluate the clinical efficacy and safety of a fixed combination of TAZ 0.05% and betamethasone dipropionate 0.05% (BM) for psoriasis vulgaris. A multicenter, randomized, single‐blinded, controlled phase 3 clinical trial was conducted. A total of 600 Chinese subjects with psoriasis vulgaris were randomized (3:1:1) to TAZ/BM cream, TAZ gel or BM cream groups for 6 weeks with an 8‐week follow up. The primary efficacy assessment end‐point was 75% improvement in Psoriasis Area and Severity Index (PASI‐75) at 6 weeks. Secondary outcome assessments included PASI‐90, percentage of PASI decrease and so forth. Safety and treatment‐related adverse events were monitored throughout the study. Our results demonstrated that the TAZ/BM group exhibited statistically significant superiority in PASI‐75 over TAZ (6.74% vs 1.67%) within 2 weeks. After 6 weeks of treatment, PASI‐75 was 44.94% in the TAZ/BM group while 19.17% and 35.00% in the TAZ and BM group, respectively. At the 8‐week follow up, the relapse rate of the TAZ/BM group was significantly lower than the BM group (10.62% vs 29.63%, P = 0.0269) though comparable with the TAZ group (10.00%). The most frequently reported treatment‐related adverse event was mild to moderate level of skin irritation events. TAZ/BM combination has significant advantages over TAZ, including satisfying efficacy, rapid onset and reduced local stimulation. Meanwhile, compared with BM, it has the advantages of longer relief time and reduced clinical relapse rate. The TAZ/BM combination drug provides psoriatic patients an alternative drug with high efficacy and low relapse rate and safety concerns.